The Emerging Role of Sfrp5 and Wnt5a in the Pathogenesis of Obesity: Implications for a Healthy Diet and Lifestyle - Koutaki, Diamanto (Nutrients, 2021)
In recent decades, the prevalence of obesity has risen dramatically worldwide among all age groups. Obesity is characterized by excess fat accumulation and chronic low-grade inflammation. The adipose tissue functions as a metabolically active endocrine organ secreting adipokines. A novel duo of adipokines, the anti-inflammatory secreted frizzled-related protein 5 (Sfrp5) and the proinflammatory wingless type mouse mammary tumor virus (MMTV) integration site family member 5A (Wnt5a), signal via the non-canonical Wnt pathway. Recent evidence suggests that Sfpr5 and Wnt5a play a key role in the pathogenesis of obesity and its metabolic complications. This review summarizes the current knowledge on the novel regulatory system of anti-inflammatory Sfrp5 and pro-inflammatory Wnt5a, and their relation to obesity and obesity-related complications. Future studies are required to investigate the potential role of Sfrp5 and Wnt5a as biomarkers for monitoring the response to lifestyle interventions and for predicting the development of cardiometabolic risk factors. These adipokines may also serve as novel therapeutic targets for obesity-related disorders.